Im Auftrag der Wahrheit Selbstpositionierungsstrategien der Philosophie im 20. Jahrhundert - Dätwyler, Maria (Brill, 2021)
What kind of arguments do 20th Century philosophers use to justify and legitimize their own discipline? By reconstructing the positioning established by the three prominent philosophical "paradigms" Phenomenology, Vienna Circle and Critical Theory, this book offers insights into the conception Western philosophy has of itself, which is still valid today.